Gastroenterological Manifestations in Individuals with Post-Covid Syndrome (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article by Sobirova G.N., «Gastroenterological Manifestations in Individuals with Post-COVID Syndrome». Alongside the well-known respiratory symptoms of SARS-CoV-2 infection, gastrointestinal complaints—particularly diarrhea, nausea, and vomiting—are frequently reported. Evidence indicates that gastrointestinal dysfunction may result both from the direct viral impact on the digestive tract and from secondary damage due to immune-mediated responses.